Pengembangan Motorik Halus Dan Kreativitas Siswa Kelas 1 Sekolah Dasar Melalui Kegiatan Membuat Gantungan Nama Pada Pembelajaran SBDP - Yuliana Anita Sari; Wasis Wijayanto (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2026)
Learning Arts, Culture, and Crafts (SBdP) in elementary schools plays an important role in developing students’ fine motor skills and creativity, especially in lower grades. This article aims to describe the development of fine motor skills and creativity of first-grade elementary school students through the activity of making name hangers from beads. This study employed a descriptive research method with a qualitative approach. The data were collected through observations of SBdP learning activities at SDN Pangonan 02, interviews with first-grade teachers, and documentation of students’ works. The results indicate that the activity of making name hangers helps improve hand–eye coordination, accuracy, and students’ creativity. In addition, this activity creates a fun and meaningful learning atmosphere for first-grade elementary school students